Precision baking: Crafting the ultimate roll cake with bôh gadông flour - Suhairi, Laili; Faudiah, Nurul; Indani; Mahyiddin, Zuraini; Atmayani, Dean Tri; Gagarin, Yuri (Bahasa Indonesia, 2025)
This study explores the underutilized potential of bôh gadông flour, derived from Dioscorea alata tubers, as an ingredient in roll cake production. Despite its abundance in certain regions, the use of bôh gadông in modern culinary applications remains limited. This research aims to address this gap by (1) standardizing roll cake recipes incorporating bôh gadông flour, (2) evaluating the organoleptic attributes (color, aroma, texture, and taste) of the cakes, (3) assessing consumer acceptance of bôh gadông flour roll cakes, and (4) analyzing the storage quality of the cakes over time. Conducted through experimental research at the Catering Laboratory of the Family Welfare Education Program, Universitas Syiah Kuala, the study employs quantitative methods. Observational data are analyzed using mean calculations, while consumer acceptance data undergo one-way ANOVA followed by LSD analysis. Results reveal that the second treatment (BG1) achieves superior scores in color, aroma, and taste. Additionally, bôh gadông roll cakes maintain satisfactory storage quality for up to two days when stored in airtight containers. These findings highlight the potential of bôh gadông flour in enhancing local culinary innovation. Future studies should explore its application in other snack varieties and include proximate testing to determine nutritional composition.